(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Endometriosis is an estrogen-dependent chronic disease characterised by ectopic implantation of functional tissue lining the uterus (endometrial glands and stroma) outside the uterine cavity. Endometriosis, a word derived from the Greek endo ’inside’, metra ’uterus’ and osis ’disease’, remains somewhat nebulous, with pelvic pain and infertility being the most common clinical symptoms. Endometrial tissue is most commonly found in the ovaries with the formation of chocolate cysts, but it can also be found in the fallopian tubes, uterosacral ligaments, gastrointestinal tract, and less commonly in the pleura, pericardium, or central nervous system [6]. Endometriosis is a disease of adolescents and women of reproductive age characterised by the presence of endometrial tissue outside the uterine cavity and often accompanied by chronic pelvic pain and infertility. In this article, we review the epidemiology of endometriosis as well as potential biomarkers for the detection and identification of risk factors that can be used in combination with biomarkers for early detection and treatment of women with endometriosis [7].